Insulin Biosynthesis: Studies of Islet Polyribosomes - Permutt, M. A. (1972)
A method is described for separation of polyribosomes from as few as 25 isolated Islets of Langerhans, representing about 250 μg of pancreatic tissue. Islets are labeled with [(3)H]leucine and polysomes are isolated with liver polyribosomes, which serve as carrier and inhibitor of ribonuclease activity. Islets incubated at 37°C for 45 min in 15.5 mM glucose, then pulsed with [(3)H]leucine, incorporated about 2-3 times more label into nascent peptides on islet polysomes than islets incubated in 2.8 mM glucose. Sucrose gradient analysis of the labeled polysomes indicated that raising the glucose concentration preferentially stimulated synthesis of peptides on trisomes and larger polyribosomes. Islets incubated with [(3)H]leucine for 15 min incorporated two-thirds of the label into proteins on membrane-bound polysomes. At least 85% of the proinsulin synthesis during this time occurs on membrane-bound polysomes.